Controls of the paleoenvironment on differential organic matter enrichment of lacustrine fine-grained rocks: A case study of the Jurassic Da'anzhai Member, central Sichuan Basin, SW China. (15th September 2022) - Liu, Ziyi; Chen, Dongxia; Lei, Wenzhi; Liu, Yang; Xie, Guangjie; Dang, Wei; Lv, Xiuxiang; Li, Sha; Yuan, Siyu
Graphical abstract: Highlights: The majority of siliceous shales in the Da'anzhai member have high TOC contents. The Da'anzhai member was deposited under oxic-suboxic conditions. OM accumulation was controlled by clastic input and sedimentation rate. The differential OM enrichment is explained by high and low clastic input models. Abstract: Organic matter (OM) is not only a source of oil and gas but also the dominant host for hydrocarbon storage in unconventional reservoirs; thus, understanding the controls on OM accumulation are of great significance for unconventional hydrocarbon exploration. Lacustrine fine-grained rocks of the Jurassic Da'anzhai Member have variable total organic carbon (TOC) contents ranging from 0.11 to 3.11 wt%. However, it is still debatable regarding mechanisms responsible for such variable enrichment. Here, we present petrological, organic, and elemental geochemical data of three wells in the Jurassic Da'anzhai Member in the central Sichuan Basin, South China. The low enrichment of redox-sensitive trace elements (MoEF, UEF, and VEF ) in lacustrine fine-grained rocks indicates oxic to suboxic conditions during deposition of the Da'anzhai Member, which are not conducive to OM preservation. The chemical index of alteration (CIA) values vary between 75 and 100, suggesting a warm/hot and humid paleoclimate. Relatively high productivity coincides with high CIA, suggesting that weathering fluxes may have played important role in the regulating primary productivity. Furthermore, the relationship between TOC and (La/Yb)N implies the influence of specific sedimentation rates on OM enrichment. Our results suggest that the OM accumulation in the Jurassic Da'anzhai Member is mainly controlled by clastic input and sedimentation rate. We propose that under conditions of variable clastic input, the appropriate sedimentation rate may have played a key role in the accumulation of OM. Finally, our study suggests that the siliceous shale may be a potential lithology for unconventional hydrocarbon production in the Jurassic Da'anzhai Member.